Regression analysis of the torque rheometer curve - Čatić, Igor; Reschner, Alfred (Polymer testing, 1985)
Elastomeric compounds based on EPDM have been examined by the Brabender Plasti-Corder torque rheometer. The torque has been measured in functional relation to the cross-linking temperature and to the type and dosage of the organic peroxide used as the crosslinking agent. The series of values of the torque from rheograms have been determined and statistically analysed by linear and nonlinear regression simultaneously, because the geometrical and comparative methods previously used are subject to the examiners' subjectivity. The magnitudes of the effects of variable factors such as temperature, type and dosage of the organic peroxide on the value of the minimum torque and the corresponding time of examination, the pre-crosslinking time and the crosslinking rate have been estimated. On the basis of the analysis of variance, conclusions have been made with regard to the main effects and significant interactions of these variable factors.